Application Tools Lean Six Sigma Definition and measurement phases in new product development. In the Electrical Industries State Company. case Study. - داود غسان قاسم; عبد الكريم عزام عبد الوهاب (Journal of Economics and Administrative Sciences, 2016)
methodology six sigma Help to reduce defects by solving problems effectively, and works Lean to reduce losses through the flow of the manufacturing process and when integrating these two methodologies (Lean and six sigma), the methodology of Lean six sigma will form the entrance to the organizers of the optimization process and increase the quality and reduce lead times and costs . by focusing on the needs of the customer. this process uses statistical tools and techniques to analyze and improve processes. We have conducted this research in the General Company for Electrical Industries and adopted its product (machine cooling water three taps) as a sample for research. In order to determine the benefits realized from the product development, according to Lean Six Sigma. When used in new product development (development time and speed the arrival of the product for the market) and the diagnosis of positive or negative effects left by the integration methodology (Six Sigma) and (Lean) on new product development in at under which the. Search to find a set of conclusions, including that the use of the design cycle (DMADV) in product development gives wide area in front of existing development to regulate the process of development can be generated from the exploitation of information from every stage of the design cycle in the subsequent stages. It can also identify the factors most important and need to be addressed to overcome the causes of product failure.